Prognostic Role of Pan-Immune-Inflammatory Value in Patients with Non-ST-Segment Elevation Acute Coronary Syndrome - Jeong Tae Byoun; Kyeong Ho Yun; Sungho Jo; Donghyeon Joo; Jae Young Cho (Journal of Cardiovascular Development and Disease)
Blood cell-derived indices are potential predictors of clinical outcomes in coronary artery disease. This study assessed the prognostic value of the pan-immune-inflammatory value (PIV) for predicting 1-year major adverse cardiovascular events (MACEs) in patients with non-ST-segment elevation acute coronary syndrome (ACS). A retrospective cohort of 1651 patients receiving percutaneous coronary intervention was analyzed. PIV, calculated from blood cell counts, was categorized with a cut-off value of 256.3 (sensitivity 60.7%, specificity 59.3%) based on receiver operating characteristic curve analysis. MACEs were operationalized as a composite of all-cause mortality, myocardial infarction (MI), stroke, any revascularization, and rehospitalization for heart failure. The incidence of MACEs was 5.0% in patients with low PIV and 9.7% in those with high PIV (log-rank p < 0.001). Multivariate analysis identified age 65 > years, renal dysfunction (eGFR < 60 mL/min/1.73 m2), and high PIV (>256.3) (HR 1.49, 95% CI 1.01–2.22, p = 0.048) as independent predictors of MACEs. Subgroup analyses revealed no statistically significant interaction between MI status or C-reactive protein levels and PIV. PIV was an independent predictor of 1-year MACEs in patients with non-ST-segment elevation ACS. It may serve as a reliable prognostic marker independently of MI or C-reactive protein levels.